Analysis of research output parameters: Density equalizing mapping and citation trend analysis - Welte Tobias; Fischer Axel; Scutaru Cristian; Groneberg-Kloft Beatrix; Kreiter Carolin; Quarcoo David (BMC, 2009)
Abstract Background Burden of disease studies indicate major socio-economic burdens since many years. They should be used for the allocation of funding. However, imbalances are present in funding policies and therefore benchmarking becomes increasingly important in health services research. Methods The present study assessed benchmarking approaches. Using large data base analyses, research was analyzed for different health research output parameters. The fields of cardiovascular and respiratory medicine served as models to assess irregular patterns of health research. For visualization, density equalizing mapping procedures were used. Results Specific areas of major research activity were identified for European countries and large differences were found. Spatial distribution of published items for cardiac and cardiovascular systems differed in comparison to the distribution for the respiratory system. In general, large countries dominated the overall number of published items. When qualitative measures such as citation analysis were assessed, differing results were achieved. In this category, mostly Scandinavian countries dominated. Conclusion The present approach of comparative output benchmarking can be used to assess institutional operating figures at the national and international level and to analyze imbalances in health and research funding.